The uncertainty of conclusions from experiments in our agricultural experiment stations - Hutto, Willis Wesley (My University, 1891)
Introduction: Along with advanced civilization and as one of its causes, comes intensive work in agricultural pursuits. A steady but rapid growth in this direction for the past few years has brought this industry to a perfection where shrewd management and strict attention to little points dictate a farmers success. It is this condition which has called science to the aid of farming. Governments have seen fit to take hold of the matter and establish institutions whose duty it is to establish old researches and conduct original experiments on all questions bearing directly on the agricultural industry of the country. The Agricultural Experiment Station was a German invention. It was introduced into the United States in 1885, the first one being established in the state of Maine. The object of our stations is to make experiments: First, on the physiology of plants and animals. Second, to analyze soils, water, and fertilizers. Third to ascertain the composition and digestibility of plants. Fourth to conduct such other experiments as have to do with the agricultural industry of the United States.
Citation: Hutto, Willis Wesley. The uncertainty of conclusions from experiments in our agricultural experiment stations. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Agriculture; Farming; Botany; Agricultural advancement; Theses; Manuscripts (documents)